(untitled) (Latakia University Journal -Basic Sciences Series, 2019)
In this search, it has been studied the properties of the magnetoacoustic soliton waves in ultra dense quantum plasma and its including ions and electrons and positrons after taking quantum effects of electrons and positrons into consideration due to their Fermionic nature and the quantum diffraction, this is by the quantum Bom potential into two momentum equations of electrons and positrons . It has been studied the solitary waves of small amplitude by using reductive perturbation method. The results have been compared to the solitary waves ones with what others have reached in related references.